Evaluating And Testing Of A Potential Dna Vaccine Against Vibrio Cholerae - Moh’d Hamadneh, Lama Abdel Qader (2003)
Although it has been more than 100 years since the first attempt to produce a cholera vaccine was made, an effective cholera vaccine has yet to be developed. In this study, the level of protection produced by a potential DNA vaccine (PVax/ctxB) was tested against the ctxB toxin of Vibrio cholerae on Balb/c mice. First, the intramuscular vaccination method was validated using pCMV plasmid that encodes HbsAg, which was detected 5 days after the injection into the tibial muscle. Next, 4 groups of mice were intramuscularly injected with either the pVax/ctxB vaccine construct or pVaxl as the negative control. The first and second groups received 2 injections spaced 3 weeks apart, while the other two groups were given 3 injections spaced 3 weeks apart. This was then followed by challenging the mice with 105 or 107 cfu/ml/mouse from clinical isolates of V. cholerae after 3 weeks of the last injection. Antibody levels for both IgG and serum IgA were monitored using ELISA, and showed high production of IgG after the first booster injection with no significant change of IgA levels.